SUBORDINASI DAN MARGINALISASI PEREMPUAN DALAM AKSES PENDIDIKAN TINGGI DI PEDESAAN: STUDI KOMPARATIF DI KABUPATEN GOWA - Firdaus (Departemen Sosiologi Aga,ma, Universitas Islam Negeri Alauddin Makassar, 2025)
This study aims to analyze the forms of subordination and marginalization experienced by women in accessing higher education in rural areas of Gowa Regency. Using a qualitative approach through case studies in six villages, this study explores the subjective experiences of female and male students in the context of gender inequality. The research findings show that strong patriarchal norms, domestic roles attached to women, and low family support are the main obstacles for women to continue their higher education. In addition, economic factors and gender-biased social constructions reinforce the marginalization of women, both structurally and culturally. Although the number of female students is increasing, their strategic role in higher education is still very limited. This study recommends the need for affirmative policies, the provision of gender-friendly educational facilities, and social change campaigns to create fair and equal access to education for women in rural areas.